Pengaruh Profitabilitas Dan Likuiditas Terdhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 (Sektor Industri Barang Konsumsi) - Khairiska Afra; Elfiswandi Elfiswandi; Muhammad Pondrinal (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of profitability and liquidity on firm value with capital structure as an intervening variable in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024. This study uses secondary data in the form of annual finansial statements with a sample of 40 companies. Firm value is proxied by price book value (PBV), profitability by Return on Assets (ROA), liquidity by Current Rasio (CR), and capital structure by Debt to Equity Ratio (DER). The analytical methods employed include descriptive statistical analysis, classical assumption tests, multiple regression analysis, path analysis, and mediation testing using SPSS version 26. The results indicate that (1) profitability has a negative and significant effect on capital structure, (2) liquidity has a negative and significant effect on capital structure, (3) profitability has a positive and significant effect on firm value, (4) liquidity has a negative and significant effect on firm value, (5) capital structure has a positive and significant effect on firm value, (6) capital stucture is not able to mediate the reletionship between profitability and firm value, and (7) capital structure able to mediate the relationship between liquidity and firm value..